Conduct Disorder, ADHD, and Disruptive Behaviour: One and the Same to Manage in the Classroom? - Sumargi, Agnes Maria; Prijonggo, Constantinus Wahju (ANIMA Indonesian Psychological Journal, 2001)
Students with Conduct Disorder (CD), Attention-Deficit/Hyperactivity Disorder (ADHD), and disruptive behaviour need to be managed differently. However, using traditional classroom behaviour management strategies to manage CD, ADHD, and disruptive behaviour do not seem effective. What appear to work well are the classroom behaviour management strategies that take into consideration the individual student's needs. This paper is going to discuss why traditional behaviour management strategies do not work effectively for students with CD, ADHD, and disruptive behaviour. Then, it is going to describe a general approach that teachers need to adopt in order to manage these behaviours effectively. Finally, this paper will present important points that teacher should consider when dealing with CD and ADHD students. Siswa-siswa dengan kelainan perilaku, Attention-Deficit/ Hyperactivity Disorder (ADHD), dan perilaku merusak membutuhkan penanganan berbeda. Namun, penggunaan strategi manajemen perilaku kelas tradisional untuk mengelola kelainan perilaku, ADHD, dan perilaku merusak tampaknya tidak efektif. Apa yang berhasil adalah strategi manajemen perilaku di kelas yang mempertimbangkan kebutuhan-kebutuhan siswa individual. Artikel ini mendiskusikan mengapa strategi manajemen perilaku tradisional tak bekerja efektif untuk siswa-siswa dengan Kelainan Perilaku, ADHD, dan perilaku merusak. Kemudian, diuraikan pendekatan umum yang perlu diadopsi para guru agar dapat mengelola perilaku-perilaku tersebut secara efektif. Akhirnya, artikel ini menyampaikan butir-butir penting yang perlu dipertimbangkan para guru bila menghadapi siswa-siswa dengan kelainan perilaku dan ADHD.